AINESSE SOCIALE ET COHABITATION INTERGÉNÉRATIONNELLE À L’ÉPREUVE DE LA GROSSESSE DE LA JEUNE FILLE [15-24 ANS] À YOPOUGON (CÔTE D’IVOIRE) - Martin, Irigo Gbété Jean (European Scientific Journal, ESJ, 2015)
This study provides information on the social bond and its transformations in the household during the gestational period of the girl in a neighborhood of Abidjan agglomeration. From a qualitative survey conducted through open interviews and a focus group, it has documented the circumstances of the occurrence of unwanted pregnancy in this age group and the relationship between celle- and that these social elders during the reproductive period. The results show that several factors contribute to the occurrence of pregnancies in the socio-environmental space Yopougon. The standard of living of the family group greatly influences intergenerational cohabitation relationships to gestational situation. In turn, it contributes to a profound degradation of assistance and social relations between younger seniors resulting in a "everyone is looking for" in the household. Reciprocal breach of commitments old cohabitation contract grudges reinforce and exacerbate tensions between cohabitants. As for seniors, the image that they have of the "enceinteur" influenced their outlook on the girl and this contributes to the cooling of the atmosphere prevailing in the family group.